T.E. Lawrence’s Idea on How to Solve the Armenian Question - Gasparyan, Naira (Armenian Folia Anglistika, 2014)
T.E. Lawrence’s specific perception of the Turks and of the Armenians is analyzed within the frames of this particular research article. T.E. Lawrence’s biographical-documentary novel The Seven Pillars of Wisdom and his famous interview given to the American journalist and editor Lincoln Steffens have been the material of our cultural and linguostylistic study. An attempt is made to establish the true image of the Young Turks and the Armenians who were killed by the Turks because of their national identity. Lawrence depicts Turkish atrocities with some highlighted negative emotion.
Keywords: cultural perceptions; linguostylistic analysis; Young Turks; Armenians; perfect massacre